Manual de los Reglamentos de Agua de Florida: Acta de Recuperación y Conservación de Recursos - Michael T. Olexa; Laura Minton; Dulcy Miller; Sarah Corbett (EDIS)
Este es el documento EDIS FE066, una publicación del Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Publicada Noviembre 2002.